Optimization of Education through Artificial Intelligence: Exploration of Types of AI and Their Contribution in Education - Wibowo, Aditya Dwi; Mudhohi, Ahmad Faqih; Wulandari, Dapita Apriani; Milah, Eli Agus; Vinanti, Caterina (Journal Collabits, 2024)
Artificial Intelligence (AI) is an increasingly developing technology that plays a crucial role in various fields, including the education system. AI can enhance the efficiency and effectiveness of the education system through various methods such as adaptive learning, predictive analysis, intelligent tutoring systems, natural language processing, and gamification. Artificial Intelligence (AI) is expected to continue to evolve. As AI has great potential to optimize and improve many aspects of human life, including education, health, business, technology, and more. Therefore, this idea is adopted by researchers to further optimize AI capabilities in the world of education and contribute to the efficiency and effectiveness of the education world. This research discusses the role of artificial intelligence in improving the efficiency and effectiveness of the education system. A literature review technique is used to collect and analyze information on this topic. The research shows that artificial intelligence can increase the efficiency and effectiveness of the education system by accelerating and facilitating the learning process, providing personalized recommendations, predicting student behavior, and improving data management.